1994
DOI: 10.1002/j.1550-8528.1994.tb00640.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Daytime and Nighttime Food Intake in an Obese Night‐Eater

Abstract: Some obese individuals consume food during awakenings from nighttime sleep. Three studies were conducted on a 28-year-old morbidly obese male with chronic sleeping complaints and insignificant weight loss, despite self-reported daily caloric restriction: I. For 3 mo, the subject recorded food intake for 24-h periods. Mean daytime intake was 1286 kcal f 386 (SD), and mean nighttime intake was 1036 kcal f 487 (SD). Caloric values of daytime and nighttime intake were negatively correlated, r = -0.22, df= 82, p<.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Mood is poorer before binge episodes than before non-binge eating episodes (Elmore & de Castro, 1989;Lingswiler, Crowther, & Stephens, 1988), or when not eating (Greeno et al, 1994;Johnson & Larson, 1982). Sleep disorders have been hypothesized to play a role in nocturnal eating (Aronoff et al, 1994;Guirguis, 1986;Nadel, 1981;Oswald & Adam, 1986;Schenck, Hurwitz, Bundlie, & Mahowald, 1991;Schenck & Mahowald, 1994). The subjective quality of sleep experienced by subjects on evenings during which nocturnal eating occurred was generally better than expected; on the whole, subjects reported that the quality of sleep they experienced was "okay."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mood is poorer before binge episodes than before non-binge eating episodes (Elmore & de Castro, 1989;Lingswiler, Crowther, & Stephens, 1988), or when not eating (Greeno et al, 1994;Johnson & Larson, 1982). Sleep disorders have been hypothesized to play a role in nocturnal eating (Aronoff et al, 1994;Guirguis, 1986;Nadel, 1981;Oswald & Adam, 1986;Schenck, Hurwitz, Bundlie, & Mahowald, 1991;Schenck & Mahowald, 1994). The subjective quality of sleep experienced by subjects on evenings during which nocturnal eating occurred was generally better than expected; on the whole, subjects reported that the quality of sleep they experienced was "okay."…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in both the fields of eating and sleep have speculated that night eating may be associated with other clinical problems. Four areas in particular have been identified, (1) overweight (Aronoff et al, 1994;Coates, 1978;Kuldau & Rand, 1986;Rand & Kuldau, 1986;Schenck & Mahowald, 1994;Stunkard, 1959Stunkard, ,1976Stunkard et al, 1955;Whyte & Kavey, 1990); (2) binge eating (Guirguis, 1986;McSherry & Ashman, 1990;Roper, 1989;Schenck & Mahowald, 1994;Williamson et al, 1989) Rand, 1986;Rand & Kuldau, 1986;Stunkard, 1959Stunkard, ,1976Stunkard et al, 1955); and (4) anxiety or negative mood (Bigsby & Muniz, 1967;Coates, 1978;McSherry & Ashman, 1990;Stunkard, 1959Stunkard, , 1976Whyte & Kavey, 1990). Systematic study of the symptom of nocturnal eating as it relates to these problems is warranted.…”
mentioning
confidence: 99%
“…In case studies behavioural treatments of NES and NEDS have been described with varying success (Aronoff, Geliebter, Hashim, & Zammit, 1994;Coats, 1978;Oswald & Adam, 1986;Williamson, Lawson, Bennett, & Hinz, 1989). One case report has shown bright light therapy to be successful (Friedman, Even, Dardennes, & Guelfi, 2002).…”
Section: Treatment Of Night Time Eatingmentioning
confidence: 96%
“…One polysomnographic study of a subject who ate while fully conscious found that he awoke to eat during stage II sleep. 106 Spaggiari et al 98 studied 10 night eaters polysomnographically; all were awake and fully aware of their eating episodes. Their awakenings occurred during NREM sleep, and they returned to sleep quickly after their ingestions.…”
Section: Differential Diagnosismentioning
confidence: 99%